Assessing the Suitability of Sodium Silicate-Activated Granite Dust in the Manufacturing of Unfired Clay Bricks - Hannington Kakande (Uganda Christian University, 2025)
This final year research and design project report provides an account of the research that was carried out from October 2024 to April 2025 in partial fulfillment of the requirements for the award of the degree of bachelor of science in civil and environmental engineering under the course unit final year research and design project. The report entails an introduction in chapter one that gives a background to the study, provides a statement of the problem, defines the objectives of the proposal in addition to stating the justification of the research and the scope of the research. In chapter two, the report provides the literature that was reviewed in order to identify the knowledge gap in the proposed research. The report also entails the employed methodology which identified the materials and methods that were used to achieve the specific objectives of research in addition to providing and discussed the results that were obtained thereafter.
Undergraduate